1999
DOI: 10.1002/hep.510300426
|View full text |Cite
|
Sign up to set email alerts
|

Primary disease recurrence after liver transplantation for alveolar echinococcosis: Long-term evaluation in 15 patients

Abstract: Between 1986 and 1991, 21 patients received liver grafts in our center for incurable alveolar echinococcosis (AE). The aim of this study was to analyze the long-term results in 15 of these 21 patients who survived more than 1 year after undergoing a liver transplantation (LT). The follow-up, mainly aimed at the diagnosis of recurrence, consisted of repeated radiological and specific immunological investigations. The role of pre- and post-LT benzimidazole (BZM) therapy was also evaluated. Among the 15 patients,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0
8

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(61 citation statements)
references
References 20 publications
4
49
0
8
Order By: Relevance
“…Liver transplantation is the last resort and should be reserved only for incurable symptomatic biliary AE cases. Cure is achieved in only half of the transplant recipients (45,46). Furthermore, immunosuppression following the transplantation can increase duplication of the parasite and lead to metastatic dissemination (12,18,47).…”
Section: Treatment and The Role Of Interventional Radiologymentioning
confidence: 99%
“…Liver transplantation is the last resort and should be reserved only for incurable symptomatic biliary AE cases. Cure is achieved in only half of the transplant recipients (45,46). Furthermore, immunosuppression following the transplantation can increase duplication of the parasite and lead to metastatic dissemination (12,18,47).…”
Section: Treatment and The Role Of Interventional Radiologymentioning
confidence: 99%
“…However, there are a number of studies that documented the outcomes for patients receiving a liver transplant because of advanced alveolar echinococcosis (45)(46)(47)211). A multicenter study performed in Europe showed an overall survival rate of 71% at 5 years, and in 58% of patients, there were no documented recurrences (211).…”
Section: Infections Caused By Echinococcus Sppmentioning
confidence: 99%
“…However, residual parasite tissue may be prone to more rapid growth because of immunosuppression and post-transplant adjuvant chemotherapy with a benzimidazole is advised [88].…”
Section: Treatmentmentioning
confidence: 99%